Kinematika Enam Derajat Kebebasan Pada Robot Bawah Air Otonom Menggunakan Pendekatan Analisa Geometri - Arvi, Muhammad Indrastata Iftitana; Endrasmono, Joko; Riananda, Dimas Pristovani; Rachman, Isa; Rinanto, Noorman; Adianto (Jurnal Elektronika dan Otomasi Industri, 2024)
Along with the expansion of Indonesian waters, maritime technology and robotics have grown significantly, making it an attractive field of technology. Autonomous Underwater Vehicle (AUV) is an autonomous underwater robot that can operate and maneuver independently based on given commands. AUVs are used in a variety of applications such as environmental monitoring, underwater infrastructure maintenance, and scientific research. To optimize AUV movement, this research develops and applies kinematics with six degrees of freedom (6-DOF) movement, namely surge, heave, sway, pitch, roll and yaw. The focus of this research is on the HYDROShips robot from the PPNS robotics team which uses 7 thruster motors to control movement in two types of kinematics: horizontal and vertical. A geometric approach is used to integrate translational and rotational movements, simplify the input given to the robot, and maximize the output on each motor. The research results show that this approach improves the efficiency and stability of the HYDROShips robot's movements, enabling the navigation of complex underwater routes with high precision. This research is expected to make a significant contribution to the development of autonomous underwater robots and improve the operational efficiency and effectiveness of AUVs in various applications.